2021
DOI: 10.1093/mnras/stab979
|View full text |Cite
|
Sign up to set email alerts
|

Stellar flares detected with the Next Generation Transit Survey

Abstract: We present the results of a search for stellar flares in the first data release from the Next Generation Transit Survey (NGTS). We have found 610 flares from 339 stars, with spectral types between F8 and M6, the majority of which belong to the Galactic thin disc. We have used the 13 second cadence NGTS lightcurves to measure flare properties such as the flare amplitude, duration and bolometric energy. We have measured the average flare occurrence rates of K and early to mid M stars and present a generalised me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 130 publications
(186 reference statements)
1
40
1
Order By: Relevance
“…Guarcello et al 2019, MacGregor et al 2021, extending across spectral types (e.g. Candelaresi, Hillier, Maehara, Brandenburg, & Shibata 2014, Jackman et al 2021) and evolutionary stages (e.g. Ilin et al 2019, 2021, Goodarzi, Mehrabi, Khosroshahi, & He 2021.…”
Section: State Of the Artmentioning
confidence: 99%
“…Guarcello et al 2019, MacGregor et al 2021, extending across spectral types (e.g. Candelaresi, Hillier, Maehara, Brandenburg, & Shibata 2014, Jackman et al 2021) and evolutionary stages (e.g. Ilin et al 2019, 2021, Goodarzi, Mehrabi, Khosroshahi, & He 2021.…”
Section: State Of the Artmentioning
confidence: 99%
“…To ensure these MV stars had similar activity levels, their stellar rotations periods were examined. The stellar rotation period can be estimated with Lomb-Scargle periodograms 55,56 This utilises a Fourier transform to calculate the relative power of periodic signatures in a timeseries. A normalised power of 1.0 would indicate a fully periodic signal, whereas 0.0 would be a signal with no periodic nature.…”
Section: Observations With Ngtsmentioning
confidence: 99%
“…In practice, any signal 9/17 greater than 0.1 is a possible periodic signature. Periods in the range 1-30 days were searched for, using a 'frequency-grid' of 20,000 evenly spaced candidate periods (following the procedure utilised by 56 to identify periods in NGTS stellar timeseries).…”
Section: Observations With Ngtsmentioning
confidence: 99%
“…Despite this predicted difference, recent work has shown that relationships between activity and rotation remain consistent from partially to fully convective stars (Wright & Drake 2016;Newton et al 2017;Wright et al 2018). Spin down is, however, believed to occur on slower timescales for fully convective stars, which accounts for the enhanced activity of mid-to-late M dwarfs (West et al 2008;Newton et al 2017;Jackman et al 2021). Therefore, rotation, activity, and the relationship between the two, are extremely useful probes of the underlying magnetic activity of ultra-cool dwarfs.…”
mentioning
confidence: 99%
“…Additionally, the recently launched Transiting Exoplanet Survey Satellite (TESS, Ricker et al (2015)) has facilitated studies of the flaring and rotating activity of cool stars (Günther et al 2020;Medina et al 2020;Seli et al 2021). Several ground-based photometric surveys, such as MEarth (Nutzman & Charbonneau 2008), the Next Generation Transit Survey (NGTS, Wheatley et al (2018)), the All-Sky Automated Survey for Supernovae (ASAS-SN, Shappee et al (2014)) and Evryscope (Law et al 2015) have also carried out detailed flare studies that include M dwarfs (West et al 2015;Mondrik et al 2018;Jackman et al 2021;Schmidt et al 2019;Martínez et al 2019;Howard et al 2019Howard et al , 2020a.…”
mentioning
confidence: 99%